Application of enhanced membrane bioreactor (eMBR) to treat dye wastewater. (May 2015) - Rondon, Hector; El-Cheikh, William; Boluarte, Ida Alicia Rodriguez; Chang, Chia-Yuan; Bagshaw, Steve; Farago, Leanne; Jegatheesan, Veeriah; Shu, Li
Graphical abstract: Highlights: We developed an enhanced membrane bioreactor (eMBR) for dye and nutrient removal. eMBR consists of 2 anoxic bioreactors, 1 aerobic membrane bioreactor, a UV-unit and a GAC column. To maintain alkalinity twice the feed flow is recirculated to anoxic reactors. More than 90% dye, COD and total nitrogen was removed by eMBR. Complete removal of dye was achieved in the GAC effluent. Abstract: An enhanced membrane bioreactor (eMBR) consisting of two anoxic bioreactors (ARs) followed by an aerated membrane bioreactor (AMBR), UV-unit and a granular activated carbon (GAC) filter was employed to treat 50–100 mg/L of remazol blue BR dye. The COD of the feed was 2334 mg/L and COD:TN:TP in the feed was 119:1.87:1. A feed flow rate of 5 L/d was maintained when the dye concentration was 50 mg/L; 10 L/d of return activated sludge was recirculated to each AR from the AMBR. Once the biological system is acclimatised, 95% of dye, 99% of COD, 97% of nitrogen and 73% of phosphorus were removed at a retention time of 74.4 h. When the effluent from the AMBR was drawn at a flux rate of 6.5 L/m 2  h, the trans-membrane pressure reached 40 kPa in every 10 days. AMBR effluent was passed through the UV-unit and GAC filter to remove the dye completely.